2008
DOI: 10.1002/ajmg.a.32307
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a locus for nonsyndromic mental retardation on chromosome 19p13

Abstract: Mental retardation (MR) occurs in approximately 3% of the population and therefore significantly impacts public health. Despite this relatively high prevalence, the specific causes of MR remain unknown in most cases, although both genetic and environmental factors are known to contribute. We describe a consanguineous family with autosomal recessive (AR) nonsyndromic MR (NSMR). Because the consanguinity of this family is complex, we explore alternative approaches for generating accurate estimates of the evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Following our initial linkage study (14), we performed wholegenome genotyping of the affected individuals and identified a shared homozygous segment that spans .2 Mb on chromosome 19p13 (Chr 19: 13 610 401-15 645 116 bp in hg Build 36.3). To facilitate the discovery of the causal mutation and gene, we included both obligate carrier parents in an exome sequencing study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following our initial linkage study (14), we performed wholegenome genotyping of the affected individuals and identified a shared homozygous segment that spans .2 Mb on chromosome 19p13 (Chr 19: 13 610 401-15 645 116 bp in hg Build 36.3). To facilitate the discovery of the causal mutation and gene, we included both obligate carrier parents in an exome sequencing study.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 71 variants (33 missense, 37 synonymous, 1 non-protein coding) in the critical region in the parents. Given the pattern of homozygosity in the critical region in Family G, we assumed that the NSMR in this family was due to a fully penetrant autosomal recessive mutation (14). Therefore, we considered 18 of the 71 variants that were heterozygous in both parents as candidates for the NSMR mutation (Supplementary Material, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A SNX13 -deficient (also called RGS-PX1) mouse was found to exhibit severe developmental defects, delayed neural tube closure, and embryonic lethality (Zheng et al 2006). Tsc13, the enoyl-CoA reductase found at the yeast NVJ, is also highly conserved in mammals as TECR, which is linked to an autosomal recessive non-syndromic intellectual disability (Nolan et al 2008). …”
Section: 4 Er-endolysosomal Mcss In Human Health and Diseasementioning
confidence: 99%